Literature Review: Perilaku Bermasalah Tidak Disiplin dalam Belajar - Sonya Antika; Amelia Putri; Risma Anita Puriani (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Indiscipline in learning behavior is a form of problematic behavior that is commonly found in the school environment and has the potential to hinder the effectiveness of the learning process. This issue does not arise suddenly; rather, it develops gradually through processes influenced by various factors. This article aims to examine the problem of indiscipline in learning through a review and analysis of relevant research findings. The study uses a literature review method by collecting, examining, and analyzing journals and scientific references that discuss learning discipline and students’ indisciplined behavior. The results indicate that indiscipline in learning activities is influenced by both internal and external factors. Internal factors include low interest and motivation, poor study habits, weak values and morals, as well as students’ physical and psychological conditions. Meanwhile, external factors include family situations, peer influence, the school environment, the use of technology, and inconsistent enforcement of rules. The observable behaviors include arriving late, skipping school without clear reasons, violating school regulations, and showing a lack of responsibility. Therefore, addressing the problem of indiscipline in learning requires a comprehensive and sustainable approach involving both schools and families.